Aerobic Exercise Improves Signs of Restless Leg Syndrome in End Stage Renal Disease Patients Suffering Chronic Hemodialysis. (6th November 2013) - Mortazavi, Mojgan; Vahdatpour, Babak; Ghasempour, Aida; Taheri, Diana; Shahidi, Shahrzad; Moeinzadeh, Firouzeh; Dolatkhah, Bahareh; Dolatkhah, Shahaboddin
Abstract : Background . Restless leg syndrome (RLS) is one of the prevalent complaints of patients with end stage renal diseases suffering chronic hemodialysis. Although there are some known pharmacological managements for this syndrome, the adverse effect of drugs causes a limitation for using them. In this randomized clinical trial we aimed to find a nonpharmacological way to improve signs of restless leg syndrome and patients' quality of life. Material and Methods . Twenty-six patients were included in the study and divided into 2 groups of control and exercise. The exercise group used aerobic exercise during their hemodialysis for 16 weeks. The quality of life and severity of restless leg syndrome were assessed at the first week of study and final week. Data were analyzed using SPSS software. Results . The difference of means of RLS signs at the first week of study and final week was - 5.5 ± 4.96 in exercise group and - 0.53 ± 2.3 in control group. There was not any statistical difference between control group and exercise group in quality of life at the first week of study and final week. Conclusions . We suggest using aerobic exercise for improving signs of restless leg syndrome, but no evidence was found for its efficacy on patient's quality of life.